US farm workers: What drives their job retention and work time allocation decisions?. (June 2017) - Luo, Tianyuan; Escalante, Cesar L
This article investigates the time allocation choices of US workers between farm work and other job alternatives. Results indicate that green card farm workers tend to allocate fewer workweeks to farm employment than citizens and undocumented workers, in favour of better opportunities in the non-farm sector. There is evidence of an assimilation effect, whereby undocumented workers also tend to re-allocate their time from farm to non-farm employment as their residence tenure increases, even though they experience constrained mobility and visibility during periods of strict immigration control. In the context of employers' violations of the existing labour laws that currently protect even the rights of undocumented workers, such turnover decisions seem justified. The findings raise concerns about whether any governmental effort to legalise the immigration status of such workers would reduce farm job turnover rates and increase farm employment retention, so long as labour standards are not enforced. Moreover, external economic shocks could more easily induce citizen and green card farm workers to abandon farm employment, whereas undocumented workers tend to remain in their farm jobs during such difficult times.